Biosurfactants from marine thermophilic bacilli for mitigating soil dehydration and preventing plant diseases - V. Zammuto; A. Macrì; M. T. Caccamo; S. Magazù; E. Conti; D. Leone; A. Spanò; C. Gugliandolo (International Journal of Environmental Science and Technology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Molecular detection of Escherichia coli virulence factors in swine isolates: A systematic review and meta-analysis - Elisa De Conti; Rodrigo C. Paiva; Brad Kuennen; Giovani Trevisan; Daniel C.L. Linhares; Annette M. O’Connor; Marcelo N. Almeida (Veterinary Microbiology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

Corrigendum to “Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets” [Applied Soil Ecology 204 (2024) 105710] - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2026)

Exploring light-effects of microalgal extract on zebrafish caudal fin cell regeneration for aquaculture applications - F. Conti; E. Frigato; E. Ruohisto; J. F. López-Olmeda; F. J. Sánchez-Vázquez; C. Baldisserotto; C. Bertolucci; S. Pancaldi (Aquaculture International, 2026)

The daily rhythms of temperature preference are conserved in nocturnal and blind fish - F. Conti; E. Gatto; G. de Alba; S. Pintos; J.F. López-Olmeda; L.M. Vera; S. Rey Planellas; S.A. Mackenzie; C. Bertolucci; F.J. Sánchez-Vázquez (Journal of Thermal Biology, 2025)

Citizen voice and state response in the context of food system transformations - Nitya Rao; Emma Marzi; Isabel Baudish; Amar Laila; Costanza Conti; Christina C. Hicks (Food Policy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2024)

P13-17 Assessment of the efficiency of the literature search of the ten key characteristics of carcinogens in the IARC Monographs evaluation process - C. Facchin; A. De Conti; L. Benbrahim-Tallaa; S. Chittiboyina; S. Ruiz; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2024)

The last cave lion of the late Upper Palaeolithic: The engraved feline of Grotta Romanelli (southern Italy) - D. Sigari; C. Bourdier; C. Conti; J. Conti; L. Forti; M. García-Diez; G. Lai; I. Mazzini; P. Pieruccini; R. Sardella (Quaternary Science Reviews, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Breast density in NF1 women: a retrospective study - R. De Santis; G. Cagnoli; B. Rinaldi; D. Consonni; Beatrice Conti; M. Eoli; A. Liguori; M. Cosentino; G. Carrafiello; O. Garrone; M. Giroda; C. Cesaretti; et al. (Familial Cancer, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by neurofibromin haploinsufficiency due to pathogenic variants in the NF1 gene. Tumor predisposition has long been associated with NF1, and an increased breast cancer (BC) incidence and reduced survival have been reported in recent years for women with NF1. As breast density is another known independent risk factor for BC, this study aims to evaluate the variability of breast density in patients with NF1 compared to the general population. Mammograms from 98 NF1 women affected by NF1, and enrolled onto our monocentric BC screening program, were compared with those from 300 healthy subjects to verify differences in breast density. Mammograms were independently reviewed and scored by a radiologist and using a Computer-Aided Detection (CAD) software. The comparison of breast density between NF1 patients and controls was performed through Chi-squared test and with multivariable ordinal logistic models adjusted for age, body mass index (BMI), number of pregnancies, and menopausal status.breast density was influenced by BMI and menopausal status in both NF1 patients and healthy subjects. No difference in breast density was observed between NF1 patients and the healthy female population, even after considering the potential confounding factors.Although NF1 and a highly fibroglandular breast are known risk factors of BC, in this study, NF1 patients were shown to have comparable breast density to healthy subjects. The presence of pathogenic variants in the NF1 gene does not influence the breast density value.

The transition from normal marine to evaporitic conditions recorded in a cold seep environment: The Messinian succession of Northern Italy - S. Conti; C. Argentino; M. Bojanowski; C. Fioroni; S. Giunti; B. Kremer; D. Fontana (Marine and Petroleum Geology, 2024)

Metronidazole Degradation by Physico-chemical and Advanced Oxidative Processes: Influence of pH and nTiO2-Functionalized Macroporous Support - Eric Sanches-Simões; Renan C. Testolin; Felipe M. Müller; Otto M. S. Gerlach; Wendell Pimentel-Almeida; Aline Dal Conti-Lampert; Albertina X. R. Corrêa; Gizelle I. Almerindo; Sergio Y. Gómez González; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Effects of tetracycline on entomopathogenic nematodes and their bacterial symbionts - M. Clausi; D. Leone; A. Strano; A. Lizio; G. Rappazzo; C. Mulder; E. Conti (Ecotoxicology, 2021)

Genetic basis of susceptibility to low‐dose paraquat and variation between the sexes in Drosophila melanogaster - Pamela C. Lovejoy; Kate E. Foley; Melissa M. Conti; Samantha M. Meadows; Christopher Bishop; Anthony C. Fiumera (Molecular Ecology, 2021)
Toxicant resistance is a complex trait, affected both by genetics and the environment. Like most complex traits, it can exhibit sexual dimorphism, yet sex is often overlooked as a factor in studies of toxicant resistance. Paraquat, one such toxicant, is a commonly used herbicide and is known to produce mitochondrial oxidative stress, decrease dopaminergic neurons and dopamine (DA) levels, and decrease motor ability. While the main effects of paraquat are well‐characterized, less is known about the naturally occurring variation in paraquat susceptibility. The purpose of this study was to map the genes contributing to low‐dose paraquat susceptibility in Drosophila melanogaster , and to determine if susceptibility differs between the sexes. One hundred of the Drosophila Genetic Reference Panel (DGRP) lines were scored for susceptibility via climbing ability and used in a genome‐wide association study (GWAS). Variation in seventeen genes in females and thirty‐five genes in males associated with paraquat susceptibility. Only two candidate genes overlapped between the sexes despite a significant positive correlation between male and female susceptibilities. Many associated polymorphisms had significant interactions with sex, with most having conditionally neutral effects. Conditional neutrality between the sexes probably stems from sex‐biased expression which may result from partial resolution of sexual conflict. Candidate genes were verified with RNAi knockdowns, gene expression analyses, and DA quantification. Several of these genes are novel associations with paraquat susceptibility. This research highlights the importance of assessing both sexes when studying toxicant susceptibility.

Molecular fossils as a tool for tracking Holocene sea‐level change in the Loch of Stenness, Orkney - Martina L. G. Conti; Martin R. Bates; Richard C. Preece; Kirsty E. H. Penkman; Brendan J. Keely (Journal of Quaternary Science, 2020)
Sediments deposited in the Loch of Stenness (Orkney Islands, Scotland) during the Holocene transgression, previously dated to between ~5939–5612 bp , were analysed for molecular fossils – lipids and chlorophyll pigments from primary producers – that complement conventional microfossil and lithological approaches for studying past sea‐level change. While microfossil and lithological studies identified a transgression between 102 and 81 cm core depth, key molecular fossils fluctuate in occurrence and concentration between 118 and 85 cm, suggesting an earlier start to the transgression. Terrestrial lipid concentrations decreased and algal‐derived, short‐chain, n ‐alkanoic acid concentrations increased at 118 cm, indicating a disruption of the freshwater lake conditions associated with the early stages of the marine transgression. The lipid and pigment analyses provided information that complements and extends that from microfossil analysis, presenting a more complete record of Holocene sea‐level changes and local vegetation changes in the Loch of Stenness. The isostatic stability of Stenness during the Holocene points towards other factors to explain the transgression, such as regional factors and/or melting of the Antarctic ice sheet (which occurred up to 3 ka).

Preservation of 34S-enriched sulfides in fossil sulfate-methane transition zones: new evidence from Miocene outcrops of the northern Apennines (Italy) - C. Argentino; J. E. Johnson; S. Conti; C. Fioroni; D. Fontana (Geo-Marine Letters, 2020)

Age-related murine hippocampal CA1 laminae oxidative stress measured in vivo by QUEnch-assiSTed (QUEST) MRI: impact of isoflurane anesthesia - Bruce A. Berkowitz; Robert H. Podolsky; Karen Lins Childers; Alexander Gow; Brandy L. Schneider; Scott C. Lloyd; Kelly E. Bosse; Alana C. Conti; Robin Roberts; Ali M. Berri; Emma Graffice; Kenan Sinan; et al. (GeroScience, 2020)
Age-related impairments in spatial learning and memory often precede non-familial neurodegenerative disease. Ex vivo studies suggest that physiologic age-related oxidative stress in hippocampus area CA1 may contribute to prodromal spatial disorientation and to morbidity. Yet, conventional blood or cerebrospinal fluid assays appear insufficient for early detection or management of oxidative stress within CA1 sub-regions in vivo. Here, we address this biomarker problem using a non-invasive MRI index of CA1 laminae oxidative stress based on reduction in R1 (= 1/T1) after anti-oxidant administration. An R1 reduction reflects quenching of continuous and excessive production of endogenous paramagnetic free radicals. Careful motion-correction image acquisition, and avoiding repeated exposure to isoflurane, facilitates detection of hippocampus CA1 laminae oxidative stress with QUEnch-assiSTed (QUEST) MRI. Intriguingly, age- and isoflurane-related oxidative stress is localized to the stratum lacunosum of the CA1 region. Our data raise the possibility of using QUEST MRI and FDA-approved anti-oxidants to remediate spatial disorientation and later neurodegeneration with age in animals and humans.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Calcium/calmodulin-stimulated adenylyl cyclases 1 and 8 regulate reward-related brain activity and ethanol consumption - Kelly E. Bosse; Farhad Ghoddoussi; Ajay T. Eapen; Jennifer L. Charlton; Laura L. Susick; Kirt Desai; Bruce A. Berkowitz; Shane A. Perrine; Alana C. Conti (Brain Imaging and Behavior, 2019)

Whale Shark Tourism: Impacts on Coral Reefs in the Philippines - C. W. Martin Wong; Inga Conti-Jerpe; Laurie J. Raymundo; Caroline Dingle; Gonzalo Araujo; Alessandro Ponzo; David M. Baker (Environmental Management, 2019)

Microparticles and autophagy: a new frontier in the understanding of atherosclerosis in rheumatoid arthritis - C. Barbati; M. Vomero; T. Colasanti; F. Ceccarelli; M. Marcosano; F. Miranda; L. Novelli; A. Pecani; Carlo Perricone; F. R. Spinelli; S. Truglia; F. Conti; et al. (Immunologic Research, 2018)

Mast cells participate in allograft rejection: can IL-37 play an inhibitory role? - Pio Conti; Alessandro Caraffa; Gianpaolo Ronconi; Spiros K. Kritas; Filiberto Mastrangelo; Lucia Tettamanti; Ilias Frydas; Theoharis C. Theoharides (Inflammation Research, 2018)

Impact of mast cells in depression disorder: inhibitory effect of IL-37 (new frontiers) - Pio Conti; Alessandro Caraffa; Gianpaolo Ronconi; Chiara M. Conti; Spiros K. Kritas; Filiberto Mastrangelo; Lucia Tettamanti; Theoharis C. Theoharides (Immunologic Research, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Potential therapeutic use of IL-37: a key suppressor of innate immunity and allergic immune responses mediated by mast cells - Pio Conti; Francesco Carinci; Gianfranco Lessiani; Enrico Spinas; Spyridon K. Kritas; Gianpaolo Ronconi; Alessandro Caraffa; Theoharis C. Theoharides (Immunologic Research, 2017)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

Altered soil carbon dynamics under different land-use regimes in subtropical seasonally-dry forests of central Argentina - G. Conti; E. Kowaljow; F. Baptist; C. Rumpel; A. Cuchietti; N. Pérez Harguindeguy; S. Díaz (Plant and Soil, 2016)

Allopatric speciation with little niche divergence is common among alpine Primulaceae - Florian C. Boucher; Niklaus E. Zimmermann; Elena Conti (Journal of Biogeography, 2016)
Aim Despite the accumulation of cases describing fast radiations of alpine plants, we still have limited understanding of the drivers of speciation in alpine floras and of the precise the timing of their diversification. Here, we investigated spatial and temporal patterns of speciation in three groups of alpine Primulaceae. Location Mountains of the European Alpine System. Methods We built a new phylogeny of Primulaceae including all species in three focal groups: Androsace sect. Aretia , Primula sect. Auricula and Soldanella . Combining phylogenetic information with a detailed climatic data set, we investigated patterns of range and ecological overlap between sister‐species using an approach that takes phylogenetic uncertainty into account. Finally, we investigated temporal trajectories of diversification in the three focal groups. Results We found that a large majority of sister‐species pairs in the three groups are strictly allopatric and show little differences in substrate and climatic preferences, a result that was robust to phylogenetic uncertainty. While rates of diversification have remained constant in Soldanella , both Androsace sect. Aretia and Primula sect. Auricula showed decreased diversification rates in the Pleistocene compared to previous geological epochs. Main conclusions Allopatric speciation with little niche divergence appears to have been by far the most common mode of speciation across the three groups studied. A few examples, however, suggest that ecological and polyploid speciation might also have played a role in the diversification of these three groups. Finally, extensive diversification likely occurred in the late Miocene and Pliocene coinciding with the later phases of the Alpine uplift, while diversification slowed down during subsequent glacial cycles of the Pleistocene.

Optical Characterization of Normal, Benign, and Malignant Thyroid Tissue: A Pilot Study - M. P. Brandao; R. Iwakura; F. S. Basilio; K. Haleplian; A. S. Ito; L. C. Conti de Freitas; L. Bachmann (Journal of Fluorescence, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Comparative safety profiles of intravitreal bevacizumab, ranibizumab and pegaptanib: the analysis of the WHO database of adverse drug reactions - C. Biagi; V. Conti; N. Montanaro; M. Melis; E. Buccellato; M. Donati; A. Covezzoli; R. Amato; L. Pazzi; M. Venegoni; A. Vaccheri; D. Motola (European Journal of Clinical Pharmacology, 2014)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Mapping of main and epistatic effect QTLs associated to grain protein and gluten strength using a RIL population of durum wheat - Veronica Conti; Pablo F. Roncallo; Valeria Beaufort; Gerardo L. Cervigni; Ruben Miranda; Carlos A. Jensen; Viviana C. Echenique (Journal of Applied Genetics, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

Variation in folate pathway genes and distal colorectal adenoma risk: a sigmoidoscopy-based case–control study - A. Joan Levine; Won Lee; Jane C. Figueiredo; David V. Conti; David J. Vandenberg; Brian D. Davis; Christopher K. Edlund; Susanne M. Henning; David Heber; Mariana C. Stern; Robert W. Haile (Cancer Causes & Control, 2011)

A case of primary papillary disseminated adenocarcinoma of canine lung - Maria Beatrice Conti; M. C. Marchesi; G. Angeli; E. Lepri; C. Marinetti; F. Rueca (Veterinary Research Communications, 2010)

Genes involved with folate uptake and distribution and their association with colorectal cancer risk - Jane C. Figueiredo; A. Joan Levine; Won H. Lee; David V. Conti; Jenny N. Poynter; Peter T. Campbell; David Duggan; Juan Pablo Lewinger; Maria Elena Martinez; Cornelia M. Ulrich; Polly Newcomb; John Potter; et al. (Cancer Causes & Control, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Olive oil adulterated with hazelnut oils: simulation to identify possible risks to allergic consumers - M. Arlorio; J.D. Coisson; M. Bordiga; F. Travaglia; C. Garino; L. Zuidmeer; R. Van Ree; M.G. Giuffrida; A. Conti; A. Martelli (Food Additives & Contaminants: Part A, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Substance P Upregulates LTB4 in Rat Adherent Macrophages from Granuloma Induced by KMnO4 - M. L. Castellani; P. Conti; M. Felaco; J. Vecchiet; C. Ciampoli; G. Cerulli; P. Boscolo; T. C. Theoharides (Neurotoxicity Research, 2009)

γ-irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: II. Effect of Oxygen and EPR Investigation - R. Dorati; C. Colonna; C. Tomasi; I. Genta; T. Modena; A. Faucitano; A. Buttafava; B. Conti (AAPS PharmSciTech, 2008)

Sedimentary filling of a wedge-top basin and relationship with the foredeep (Middle Miocene Marnoso-arenacea Formation, northern Apennines) - Stefano Conti; Daniela Fontana; Corrado C. Lucente (Facies, 2008)

Clinical findings and diagnosis in a case of cholangiocellular carcinoma in a horse - M. B. Conti; M. C. Marchesi; F. Zappulla; D. Buttarelli; E. Lepri; F. Passamonti; S. Galletti; G. Rucco; F. Rueca (Veterinary Research Communications, 2008)

γ-Irradiation of PEGd,lPLA and PEG-PLGA Multiblock Copolymers: I. Effect of Irradiation Doses - R. Dorati; C. Colonna; M. Serra; I. Genta; T. Modena; F. Pavanetto; P. Perugini; B. Conti (AAPS PharmSciTech, 2008)

Assessment and Behavior of Alphafetoprotein (AFP), Antigen Cancer 15/3 (CA 15/3), Carcinembryonal Antigen (CEA) in Clinical Oncology of the Dog: Preliminary Study - M.C. Marchesi; M.B. Conti; C. Pieramati; V. Mangili; G. Fruganti (Veterinary Research Communications, 2007)

5-Methyl-Pyrrolidinone Chitosan Films as Carriers for Buccal Administration of Proteins - C Colonna; I Genta; P Perugini; F Pavanetto; T Modena; M Valli; C Muzzarelli; B Conti (AAPS PharmSciTech, 2006)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

Floral Odor Variation in Two Heterostylous Species of Primula - Anne C. Gaskett; Elena Conti; Florian P. Schiestl (Journal of Chemical Ecology, 2005)

Expression of the ?-carotene desaturase gene in sunflower - M Fambrini; M Salvini; A Conti; V Michelotti; C Pugliesi (Plant Biosystems, 2004)

Blood Pressure Measurements in Dogs and Horses Using the Oscillometric Technique: Personal Observations - F. Porciello; F. Birettoni; M.B. Conti; C. Marinetti; M.T. Antognoni; G. Fruganti (Veterinary Research Communications, 2004)

Oxygen supply modulates MCP-1 release in monocytes from young and aged rats: Decrease of MCP-1 transcription and translation is age-related - M. Reale; C. Di Giulio; M. Cacchio; R.C. Barbacane; A. Grilli; G. Bianchi; M. Di Gioacchino; M. Felaco; P. Conti (Molecular and Cellular Biochemistry, 2003)

Inhibition of MCP-1 and MIP-2 transcription and translation by mimosine in muscle tissue infected with the parasite Trichinella spiralis - Pio Conti; Stavros Frydas; Marcella Reale; Renato C. Barbacane; M. Di Gioacchino; M. Felaco; A. Trakatellis (Molecular and Cellular Biochemistry, 2002)

Genetic Analysis of Neoplasia Induced by N-Nitroso-N-methylurea in Xiphophorus Hybrid Fish - Steven Kazianis; Irma Gimenez-Conti; David Trono; Anthony Pedroza; Lori B. Chovanec; Donald C. Morizot; Rodney S. Nairn; Ronald B. Walter (Marine Biotechnology, 2001)

A Proposed Classification Scheme for Xiphophorus Melanomas Based on Histopathologic Analyses - Steven Kazianis; Richard B. Setlow; John C. Harshbarger; Arvil D. Woodhead; Ronald B. Walter; Rodney S. Nairn; Irma Gimenez-Conti (Marine Biotechnology, 2001)

Influence of feeding precursors on tropane alkaloid production during an abiotic stress in Datura innoxia transformed roots - M. Boitel-Conti; J-C. Laberche; A. Lanoue; C. Ducrocq; B.S. Sangwan-Norreel (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Impact of extremely low frequency electromagnetic fields on CD4 expression in peripheral blood mononuclear cells - Mario Felaco; Marcella Reale; Alfredo Grilli; Maria A. De Lutiis; Renato C. Barbacane; Silvano Di Luzio; Pio Conti (Molecular and Cellular Biochemistry, 1999)

RFLP mapping of quantitative trait loci controlling abscisic acid concentration in leaves of drought-stressed maize (Zea mays L.) - R. Tuberosa; M. C. Sanguineti; P. Landi; S. Salvi; E. Casarini; S. Conti (Theoretical and Applied Genetics, 1998)

Effect of polyions on the early events of Sindbis virus infection of Vero cells - P. Mastromarino; C. Conti; R. Petruzziello; R. Lapadula; N. Orsi (Archives of Virology, 1991)

Identification of lipid components of human serum lipoproteins involved in the inhibition of Sindbis virus infectivity, hemagglutination, and hemolysis - P. Mastromarino; C. Conti; S. Rieti; N. Orsi (Archives of Virology, 1988)

Characterization of rat brain cellular membrane components acting as receptors for vesicular stomatitis virus - C. Conti; P. Mastromarino; M. G. Ciuffarella; N. Orsi (Archives of Virology, 1988)

Inhibition of rabies virus infection by a soluble membrane fraction from the rat central nervous system - C. Conti; B. Hauttecoeur; M. J. Morelec; B. Bizzini; N. Orsi; H. Tsiang (Archives of Virology, 1988)

Different patterns of replication in influenza virus-infected KB cells - G. Conti; P. Valcavi; A. Natali; G. C. Schito (Archives of Virology, 1980)